(3x+3)+(15-3x)=

Simple and best practice solution for (3x+3)+(15-3x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+3)+(15-3x)= equation:


Simplifying
(3x + 3) + (15 + -3x) = 0

Reorder the terms:
(3 + 3x) + (15 + -3x) = 0

Remove parenthesis around (3 + 3x)
3 + 3x + (15 + -3x) = 0

Remove parenthesis around (15 + -3x)
3 + 3x + 15 + -3x = 0

Reorder the terms:
3 + 15 + 3x + -3x = 0

Combine like terms: 3 + 15 = 18
18 + 3x + -3x = 0

Combine like terms: 3x + -3x = 0
18 + 0 = 0
18 = 0

Solving
18 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7(2n+2)=7(7n+7)+9 | | 4(q)+(-1)(1-q)=1(q)+2(1-q) | | -4n(6n-5)+3n= | | 5(x+3)=4x+14 | | 0.9x-5.3=0.1 | | (9x-6)+6= | | 2+-6m=-4m+10 | | -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 | | 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b | | K-12=11 | | b/2=-7 | | 4b+3a= | | 1-2r=9-r |

Equations solver categories